Atypical presentations of pulmonary tuberculosis diagnosed by fibreoptic bronchoscopy. Issue 814 (August 1993) - Jayasundera, C. I.; Attapattu, M.; Kumarasinghe, M. P.
Abstract : A total of 356 patients were subjected to fibreoptic bronchoscopy from September 1989 to June 1991 to exclude bronchial carcinoma. Bronchial biopsy, bronchial brush smears and bronchial wash were obtained. Bronchial wash was examined for acid fast bacilli (AFB) compatible with Mycobacterium tuberculosis. The total number diagnosed as pulmonary tuberculosis by fibreoptic bronchoscopy was 21(5.8%). The sputum smears were negative for AFB in all these patients. Previous studies have shown the importance of fibreoptic bronchoscopy in suspected cases of tuberculosis where the sputum smear is negative. This study is further evidence of the importance of routine examination of bronchial wash for AFB in all cases undergoing fibreoptic bronchoscopy to detect atypical cases of pulmonary tuberculosis.